STEREO-PHOTOGRAMMETRIC MEASUREMENT OF SPATIO-TEMPORAL VELOCITY FIELDS AT LANGE GLACIER, KING GEORGE ISLAND - Schwalbe, Ellen; Koschitzki, R.; Johnson Gavilan, Erling John; Schröter, Benjamin; Mojica, Diego; Gino Casassa; Cardenas Mansilla, Carlos Alberto; Hans‐Gerd Maas (My University, 2020)
Abstract. A network consisting of six cameras was set up on both sides of Lange Glacier on King George Island, Antarctica, for a period of two years to monitor changes in the glacier’s motion behaviour. The cameras were observing spatio-temporal glacier surface velocity vector fields as well as the position of the glacier front. Velocity field information was obtained from image sequences by applying subpixel accuracy photogrammetric image sequence analysis techniques. Georeferencing in a superordinate coordinate system was performed via integrated photogrammetric-geodetic network adjustment. As a result, velocity fields were determined with maximum glacier surface velocities in the order of 1.5 meter per day. The results of terrestrial camera image sequence processing can be used as validation and calibration reference for satellite image based glacier velocity dynamics calculations. Moreover, the very high temporal resolution of the image sequences taken at 20 minute time intervals can also be used to analyse highly dynamic processes.